Antiinflammatory and antioxidant activities of a polyphenol‐rich extract from Zizyphus lotus L fruit pulp play a protective role against obesity. Issue 6 (1st October 2018) - Ghalem, Meriem; Murtaza, Babar; Belarbi, Meriem; Akhtar Khan, Naim; Hichami, Aziz
Abstract: Zizyphus lotus (Zl) is used widely as a source of food and for the treatment of various ailments. Therefore, we investigated the biological activities of Zl against obesity and related disorders. Hence, male Wistar rats received either control diet, high fat diet (HFAD), or HFAD supplemented with the Zl pulp (HFADP) for 14 weeks. RAW 264.7 cells were used for the determination of antiinflammatory activities in vitro. It was observed that HFDP resulted in significantly reduced weight, blood sugar, and oxidative stress than HFAD. In addition, Zl extract co‐treatment with LPS reduced the mRNA expression of MCP‐1, pro‐inflammatory cytokines (IL‐6, TNF‐α), and increased the level of IL‐10, an antiinflammatory cytokine, in LPS‐stimulated RAW 264.7 cells. Moreover, nitric oxide synthesis and the expression of iNOS were decreased by Zl extract in RAW 264.7 cells. Zl extract also possessed a significant antioxidant capacity and ferric‐reducing power. Our results validate the traditional use of Zl. Practical applications: Zizyphus lotus is commonly used as food in different countries and is easily available. Scientific validation of the traditional use of plants can be significant in the prevention and treatment of different disorders. Naturally occurring products are generally safe to use, have fewer side effects, and can be self‐administered. Hence, specialized health‐care supervision is not necessary. Our study supports the traditional use of Zizyphus lotus to prevent and decrease obesity and related disorders.